Effect of heat treatments on the drying behaviour, moisture content and oil yield of Balanite aegyptiaca Kernels - Abel, Grace Igbele (Array, 2020)
The influence of different heat treatments,including oven drying at 40, 50, 60 and 70°C for 60, 120 and 180 minutes ateach temperature,roasting, boiling for 5, 10, and 15 minutes,sun and solar drying for 480 and 720 minutes,on the drying behaviour, moisture content and oil yield of Balanite aegyptiacakernels (BaKs) was investigated.The moisture contentson wet basis were determined by the oven drying method at 105C for 4 hours and calculated from both weight loss data anddry solid weight of the kernel samples,while oil was extracted with n-hexane using Soxhlet apparatus. The experiments were conducted in triplicates.Low moisture contents of 2.726 and 2.426% at drying times of 60 and 120 minutes were obtained in Balanites aegyptiaca kernelsdried at 70C,while drying at 40, 50 and 60C for 180 minutes gave low moisture contents of 3.973, 3.861 and 3.779%,respectively. The drying of Balanite aegyptiacakernels occured in the falling rate period. The moisture contents of Balanites aegyptiaca kernelsoven-dried at 40, 50, 60 and 70C decreased with increasing drying time when compared to the raw kernels. Similarly, the average oil yield of Balanite aegyptiaca kernels decreased with increasing temperature in the following order: raw>40C>50C>60C>70 C. The highest oil yield (45.345%)was obtained in the boiled kernels and the least oil yield (37.790%) in those kernels dried at 70 C. Results from thisstudy justify the use of boilingin traditional Balanite kernel oil extraction process as it gave the highest oil yield.